Experimental study of mechanical properties of sisal/jute fibers hybrid sandwich composite. (2022) - Balamurugan,; Girimurugan, R.; Muthuraj, M.; Hasane Ahammad, S.K.; Vijayakumar, N.; Appadurai, M.
Abstract: The objective of this research is to examine the mechanical characteristics of a composite material made from Jute fiber (JF) and sisal fiber (SF) for use in orthopedic long bone plates. JF/epoxy forms the exterior layers of the JF/SF hybrid composite, whereas SF/epoxy forms the inside layers. Similarities between the composite plate and the skeleton have been noted (spongy interior cancellous matrix and rigid exterior cortical). Samples of the manufactured hybridized sandwich composites were subjected to experimentation for finding tensile, micro hardness, compressive and flexural testing to determine their mechanical properties. The experimentation is made on the standard test specimen. In addition, the contact angle (CA) and water absorption of the Sisal Fiber/epoxy and Jute Fiber/Sisal Fiber/epoxy composites is determined to get a better idea of their wettability. In addition, the ethanol infiltration technique was used to calculate the porosity of the JF/SF compo sites scaffold specimen. The mechanical tests reveal that the JF/SF hybridized composites have a bending strength of 345 MPa, UTS of 148 MPa, and a compressive strength of 382 MPa; moreover, the bending tests reveal a Young's modulus of (21.56 GPa), which is higher than the tensile modulus (6577 MPa) and compressive modulus (2047 MPa). Research into the scaffolds' wettability revealed that the JF/SF composites were hydrophobic (CA = 92.41), absorbing 3.436% less water than the SF/composites (6.953%). Hydrophilicity (CA = 54.28 ± 1.71) is evident in SF composites. The results of the experiments show that the JF/SF hybrid composite has potential as a bone fracture plate material in orthopedics.